THE SITUATION OF SMOKING AND THE KNOWLEDGE, ATTITUDE ON THE HARDS OF SMOKING AMONG STUDENTS OF LE TRUNG DINH HIGH SCHOOL, QUANG NGAI CITY, 2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: To find out students’ knowledge and attitudes about the Effects of smoking, the smokingstatus of students.Method: A cross-sectional descriptive study was carried out on 432 students from Le Trung DinhHigh School, Quang Ngai City, from October 2022 to June 2023.Results and conclusion: Student smoking status: The percentage of students currently smoking is5.1%). The percentage rate of male students who smoke accounted for 6.1% and female studentswho smoked accounted for 4.0%. Students’ knowledge about the harmful effects of tobacco: Thepercentage of students who have correct knowledge about the harmful effects of smoking was 79.2.The percentage of students who think that smoking can be is 89.4 and smoking is harmful to healthwas 93.1 The percentage of students who know about the Law on Prevention and Control of TobaccoHarms is 50.9 The percentage of students who think that under 18 years old smoking will be fined is50.9%. Students’ attitudes about the harmful effects of tobacco: The percentage of students who havea positive attitude about the detrimental effects of tobacco is 78%. When seeing other people smoking,91.2% feel uncomfortable and do not accept it. 8.8% of the students felt normal. The percentage ofstudents who do not smoke when invited to smoke by friends is 81%; 84.3% of students alwaysintend to advise friends and relatives to quit smoking. There are 89.4% think that parents should bantheir children from smoking and 88.4% think smoking is a bad habit.
Keywords: Smoking, knowledge, attitude, students at Le Trung Dinh High School.